2019
DOI: 10.1109/jlt.2019.2905630
|View full text |Cite
|
Sign up to set email alerts
|

The Resilience of Hermite– and Laguerre–Gaussian Modes in Turbulence

Abstract: Vast geographical distances in Africa are a leading cause for the so-called "digital divide" due to the high cost of installing fibre. Free-Space Optical (FSO) communications offer a convenient and higher bandwidth alternative to point-topoint radio microwave links, with the possibility of re-purposing existing infrastructure. Unfortunately, the range of high bandwidth FSO remains limited. While there has been extensive research into an optimal mode set for FSO to achieve maximum data throughput by mode divisi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 67 publications
(28 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…The symmetry of low-order HG modes means that they are invariant to lateral displacements [136]. Even with the additional higher-order effects of turbulence, it has been experimentally shown that HG modes are more resilient than LG (or OAM) modes [137]. An excerpt of the crosstalk results of LG versus HG modes in shown in Fig.…”
Section: B the Robustness Of Structured Lightmentioning
confidence: 98%
“…The symmetry of low-order HG modes means that they are invariant to lateral displacements [136]. Even with the additional higher-order effects of turbulence, it has been experimentally shown that HG modes are more resilient than LG (or OAM) modes [137]. An excerpt of the crosstalk results of LG versus HG modes in shown in Fig.…”
Section: B the Robustness Of Structured Lightmentioning
confidence: 98%
“…LG modes are orthogonal to each other, which makes them a potential modes of choice for SMM. Although previous reports have shown that Hermite Gaussian mode basis may, on average, outperform LG in terms of turbulence resilience [13], [14], we choose LG basis due to its cylindrical symmetry, and, hence, more straightforward generation and process in practice. In a cylindrical system coordinates (r, φ, z), the electric field of an LG mode with radial and azimuthal indices p and , respectively, can be represented as follows [15]…”
Section: A Laguerre-gaussian Mode Basismentioning
confidence: 99%
“…In addition, in the existence of a restricted aperture, LG modes have a higher information capacity, more robust against rotation of the beam that cannot affect the detection than HG modes. 51 LG beams as unique information carriers are selected to enhance the degree of freedom for transmitting signals and data encoding in both the amplitude and phase that provides more reliability to the system under severe atmospheric turbulence. 35 Despite the rapid improvement of the architecture design of PON in MDM-based hybrid PON/FSO systems, PON architecture is still a relatively uncovered domain in the recent next-generation access networks.…”
Section: Introductionmentioning
confidence: 99%